ASSESSMENT OF VERTEBRATE DIVERSITY IN ALABATA NATURE RESERVE ABEOKUTA, SOUTH-WEST NIGERIA (2011)
The importance of wildlife, especially the vertebrates for game, tourism and medicinal use cannot be over emphasized. Nature reserves are also known to influence the ecosystem of its location. However, rapid increase in land use for agriculture and other physical developments are gradually reducing wildlife habitation including the Alabata area nature reserve of Abeokuta. Inventory of these resources in relation to their habitat parameters would inform their better management. Assessments of vertebrate and associated flora diversities were therefore carried out in Alabata Nature Reserve. The study covered 20 km2 out of 97.3 km2 area of Alabata Nature Reserve. Twenty sample plots each of 25m x 25m were laid randomly. Animals, vegetations, soil and level of human interference were assessed for 24 months in each plot cutting across wet and dry seasons. Animals were surveyed weekly using the King Census and Line Transect methods, by direct and indirect modes. Vegetation was surveyed using the Point Center Quarter method. Soil samples were collected randomly with auger at 0-15cm, 15-30cm and 30-45cm depth; air-dried and analysed for pH, Organic Carbon (OC), nitrogen and Particle Size (PS) distribution using standard methods. Structured questionnaires were randomly administered to 20 residents in the farm settlements adjoining the study site to assess the level of human interference. Data were analyzed using descriptive statistics, Dominance, Shannon Weiner, principal component as well as Simpson, Evenness and Equitability indices. Forty species of wild vertebrate belonging to thirty-one families were encountered at the study site. Thryonomys swinderianus was the most abundant vertebrate species with a mean frequency of 319±40.8, followed by Xerus erythropus (143±2.9) and Arvicanthus niloticus (122±15.3) while Ploceus capensis (5±3.9) was the least abundant. Daniellia oliveri (1123±4.6) was the most abundant tree species, followed by Anona senegalensis (270±3.9) and Bridelia micrantha (179±3.5). Mean soil pH value was 5.4±0.2 and 6.6±0.3 during the wet and dry seasons respectively. The OC of the soil ranged from 13.2% to 66.8%, while nitrogen content was from 0.8% to 7.5% and mean PS was from 3.2±0.2 to 90.4±4.5. Hunting intensity was perceived to be low (20.0%), although burning due to stray fire was perceived to be high (46.0%) in the site. The animal species diversity indices were Shannon Weiner (0.6), Simpson Index (0.9), Evenness (0.4), Dominance (0.004) and Equitability (0.9) for the wet season. and Shannon Weiner (0.6), Simpson Index (0.9), Evenness (0.4), Dominance (0.005) and Equitability (0.9) for the dry season.The plant species diversity indices were Shannon Weiner (0.6), Simpson Index (0.9), Evenness (0.5), Dominance (0.005) and Equitability (0.9) for wet season and Shannon Weiner (0.6), Simpson Index (0.9), Evenness (0.6), Dominance (0.9) and Equitability (0.9) for dry season. The principal component analysis and ordination showed that the studied ecosystem was not stable. Diversity of vertebrate species in Alabata Nature Reserve was high. Abundace of Thryonomys swinderianus and Xerus erythropus can be attributed to adequate food and cover provided by trees. However, wildfire which is the greatest threat has to be controlled for the reserve to realize its full potentials.